A review of rock slope failures in Malaysia: Exploring types, cases, causes, and consequences - Mohd Taha, Aidatul Izana; Mohamad Abdullah, Nazirah (Universitas Mercu Buana, 2025)
Rock slope failures remain a significant concern in regions of Malaysia with varying geological formations. This review examines the challenges posed by these incidents and addresses key knowledge gaps. By providing a comprehensive, multidisciplinary analysis of case studies, technological advancements, climate influences, disaster management, and socio-economic impacts, it offers valuable insights for researchers, engineers, and policymakers. It examines key failure types, including rock falls, slides, avalanches, and general failures, through notable case studies such as Bukit Lanjan (Selangor), Kinta Valley (Perak), and Mount Kinabalu (Sabah). A comprehensive methodology framework was employed, utilizing manual search techniques (handpicking, snowballing, citation, and reference tracking) alongside advanced keyword-based searches with Boolean operators in Scopus, ScienceDirect, and Google Scholar databases. Findings reveal that Malaysian rock slopes are highly susceptible to collapse due to heavy rainfall, human activities, and natural events such as earthquakes. While these factors can act independently, their combined effects significantly amplify failure risks, particularly during intense rainfall. The consequences extend beyond immediate casualties, injuries, and property damage, leading to infrastructure failures, economic disruptions, and environmental degradation. This review underscores the need for sustainable mitigation strategies to address these risks and highlights the urgency of implementing effective solutions to safeguard lives, infrastructure, and ecosystems.